2019
DOI: 10.1088/1755-1315/344/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of a river water flow under seasonal conditions: Case study

Abstract: Precipitation regime and anthropogenic activities are the main factors that influence the river flow along the time. To assure the flow regulation and the flood mitigation some structural measures must be implemented. Building dams represents one of these measures. Their impact on the stream flow and climate change must be studied for avoiding negative effects on the environment. Therefore, our study focuses on the variability of the Buzau River (in Romania) water flow and its seasonal variation. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Compared to the results obtained in [38] by utilizing the IHA methodology, the present article provides new insights into the series variability by building IMFs. The output of this study is in concordance with the finding of [39], indicating the significant alteration in the river flow after building the dam, emphasized by the differences between the IMFs' amplitudes and frequencies corresponding to S1 and S2. Meanwhile, in [38], it was shown that a decrease of 12.6% in the maximum monthly discharge was noticed after 1984 with respect to 1955-1983, and in the same period, the minimum and the maximum of the 90-day maximum flow decreased from 28.6 to 16.4 m 3 /s, and from 92.6 to 69.8 m 3 /s, respectively, but no chart of the time series components is provided.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Compared to the results obtained in [38] by utilizing the IHA methodology, the present article provides new insights into the series variability by building IMFs. The output of this study is in concordance with the finding of [39], indicating the significant alteration in the river flow after building the dam, emphasized by the differences between the IMFs' amplitudes and frequencies corresponding to S1 and S2. Meanwhile, in [38], it was shown that a decrease of 12.6% in the maximum monthly discharge was noticed after 1984 with respect to 1955-1983, and in the same period, the minimum and the maximum of the 90-day maximum flow decreased from 28.6 to 16.4 m 3 /s, and from 92.6 to 69.8 m 3 /s, respectively, but no chart of the time series components is provided.…”
Section: Discussionsupporting
confidence: 88%
“…The current analysis provides a comprehensive and nuanced view of the dam's impact on Buzău discharge dynamics, validating and complementing the findings from the articles [38,39]. While the research conducted in [39] only tested for the existence of a trend in the annual and quarterly flow series and built an AR(5) model to forecast the mean quarterly series, the present study has a larger scope. With a higher-resolution data series, it can detect monthly seasonality factors.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our research aims to answer whether the Buzău River discharge is altered after putting the Siriu Dam, one of Romania's most important accumulation lakes in the country, into operation. Two articles [36,37] attempted to answer this question by testing different statistical hypotheses and using indicators of hydrologic alterations (IHA). Two models (regression and generalized regression neural network) [37,38] for the daily river discharge have also been proposed, but neither of them was satisfactory from an accuracy viewpoint.…”
Section: Introductionmentioning
confidence: 99%